Income and wealth: Series XI : Studies on short-term national accounts and long term economic growth (London : Bowes and Bowes Publishers Ltd, 1965)
This paper represented a series of attempts to evaluate the national income statistics of developing countries, to identify sources of bias, to adjust the estimates where possible, and to find economic explanations for the rates of growth which seemed to emerge after this kind of systematic examination.
osa; 03/12/18
Loans
Keywords: Phyllis Deane; National income; Economic development